Technologies and innovation : 4th International Conference, CITI 2018, Guayaquil, Ecuador, November 6-9, 2018, Proceedings /: 4th International Conference, CITI 2018, Guayaquil, Ecuador, November 6-9, 2018, Proceedings. (2018) - Unknown
No abstract available